Carbamazepine removal from wastewater and the degradation mechanism in a submerged forward osmotic membrane bioreactor. (October 2020) - Yao, Meichen; Duan, Liang; Wei, Jian; Qian, Feng; Hermanowicz, Slawomir W.
Highlights: The removal of contaminants was the combination of rejection and biodegradation. 14 Degradation products were tested and 7 possible pathways were speculated. Delftia could be the characteristic bacteria that degraded CBZ. Abstract: A submerged forward osmotic membrane bioreactor (FOMBR) was used to reveal the removal and degradation mechanism of carbamazepine (CBZ) from wastewater. The results showed that the removal mechanism consisted of the rejection of the forward osmotic (FO) membrane and biodegradation of the activated sludge. The removal efficiencies of COD, NH4 + -N, and CBZ by the FOMBR were approximately 94.77%–97.45%, 93.56%–99.28%, and 88.20%–94.45%, respectively. Moreover, the COD and NH4 + -N removal efficiencies were positively correlated with the increased CBZ concentrations. The results of the soluble microbial products (SMP) and extracellular polymeric substances (EPS) tests illustrated that the membrane fouling potential of EPS may be higher than that of SMP. According to the identified 14 degradation products, oxidation, hydroxylation, and decarboxylation were defined as the primary CBZ degradation mechanism. In addition, the RNA results showed that Delftia could be the characteristic bacteria in the CBZ degradation process.